Challenges of industrial development of Serbia - Jakopin Edvard; Bajec Jurij (Panoeconomicus, 2009)
Built upon education ideologies of the previous century, development of Serbian industry is not able to meet global demands of the modern, 21st century market. Innovative ongoing processes in technology and all industrial branches are global and ever more rapid, and they are circumventing the SEE region. The economic structure of Serbian industry at the beginning of transition was two decades old. At the beginning of 2009, after eight transition years, a short economic transition summary is as follows: the trailing caused by the events of the 1990s is very hard to cope with and we are only half through with this task; on the other hand, we are lagging behind EU-15 and EU-10 more and more. Apart from the analysis of structural non-adjustment of the industrial system and its impact on the macroeconomic balance, the paper underlines a significant role of the state in the formulation of industrial policy.